Non-specialist tool to assess the vulnerability of residential structures against natural hazards - Manalese, Glenn Matthew G.; Pacheco, Benito M.; Aquino, Diocel Harold M.; Orozco, Christian R. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
The Philippines, owing to its geographical and geological situation, is constantly battered by multiple natural hazards every year. Hence, it is of utmost importance for the citizens of the country to be always prepared. Developing an application that would raise the awareness of citizens against the danger posed by natural hazards would be one way of achieving this. The application evaluates the vulnerability of the user's house using the vulnerability curves generated by the Institute of Civil Engineering in 2013 for the Greater Metropolitan Manila Area Risk Analysis Project. Implemented using Google's suite of applications, the web app identifies the building type of a house and evaluates its damage index based on the vulnerability curves. Unbeknownst to the user, this data is also collected and managed in a database for research purposes. This data has been used to create a map of vulnerable houses. And finally, a survey at the end of the web app collected user feedback on the application. Statistical analysis of this feedback shows that more than half of the users think that the app is 'good' or 'excellent' in terms of its usability, user friendliness, interface design, and ease of conveying information.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Hazard mitigation -- Philippines; Web applications; Project Safehouse